Physical activity promotion in Manitoba: Strengths, needs, and moving forward. (January 2019) - Kosowan, Leanne; Wener, Pamela; Holmqvist, Maxine; Gonzalez, Miriam; Halas, Gayle; Rothney, Janet; Katz, Alan
Objectives: To present findings of a workshop with physical activity professionals in Manitoba, Canada, to facilitate the enhancement of physical activity promotion efforts by exploring (1) effective physical activity strategies, (2) methods to strengthen physical activity strategies, (3) challenges in implementing physical activity strategies in Manitoba, and (4) strategies to support collaboration. Methods: The Manitoba Research Chair in Primary Prevention hosted a workshop for 54 stakeholders in Manitoba. Qualitative and quantitative data obtained from the workshop were analyzed using qualitative content analysis and univariate descriptive analysis. Purposive sampling was used to recruit participants with diverse experiences in physical activity promotion. Results: Strategies were identified and presented according to the socioecological model. Community assessment and community engagement, regional partnerships, capacity building, and mitigation of barriers characterized the discussion. In addition, discussions emphasized the need for the consistent and comprehensive application of a provincial physical activity action plan. The workshop ended with a discussion of the importance of collaboration to improve physical activity programs and initiatives. Conclusion: Several common needs were identified that reflect topics from the broader literature. Collaborations and insights from workshop participants provide direction to target increased physical activity support and programming across disciplines, sectors, and regions.